2005
DOI: 10.1111/j.1365-2966.2005.09024.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and evolution of low-mass W Ursae Majoris type systems - III. The effects of the spins of the stars

Abstract: In a previous paper, using Eggleton's stellar evolution code, we have discussed the structure and evolution of low‐mass W Ursae Majoris (W UMa) type contact binaries with angular momentum loss owing to gravitational radiation or magnetic braking. We find that gravitational radiation is almost insignificant for cyclic evolution of low‐mass W UMa type systems, and it is possible for angular momentum to be lost from W UMa systems in a magnetic stellar wind. The weaker magnetic activity shown by observations in W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…Although it seems probable that energy transfer occurs in the common envelope of W UMa systems, it is not clear at present where and how the transfer takes place in the common envelope. The structure and evolution of W UMa contact binaries have been investigated by several authors in recent years (Kähler 2002a,b; Li, Han & Zhang 2004, 2005; Yakut & Eggleton 2005). It is found that loss of contact is avoided if the energy transfer is assumed to be sufficiently effective (Kähler 2002a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Although it seems probable that energy transfer occurs in the common envelope of W UMa systems, it is not clear at present where and how the transfer takes place in the common envelope. The structure and evolution of W UMa contact binaries have been investigated by several authors in recent years (Kähler 2002a,b; Li, Han & Zhang 2004, 2005; Yakut & Eggleton 2005). It is found that loss of contact is avoided if the energy transfer is assumed to be sufficiently effective (Kähler 2002a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Based on a rate of angular momentum loss (AML) owing to magnetic stellar winds of Hurley et al [4], we have investigated the non-conservative evolution of W UMa systems [8], and a evolutionary model is shown in Figure 2. It is seen in Figure 2 that the rate of AML in contact evolution is much lower than that in non-contact stage, which is consistent with the results predicted by observations and a polytropic model developed by Rucinski [12].…”
Section: Structure and Evolution Of W Uma-type Systemsmentioning
confidence: 99%
“…We also investigated the merger of W UMa systems with an extreme mass ratio and well-determined physical parameters recently, it is found that a large amount of mass and angular momentum should be lost from binary systems, otherwise, the rotation velocities of merged single stars would exceed their breakup velocities [6]. The time dependence of contact degree F, effective temperature T eff of the primary (solid) and the secondary (dashed), together with the ratio of spin angular momentum to orbital angular momentum J rot /J orb , the luminosity transfer rate ∆L, the total mass, M tenv , contained in convective envelopes, and rate of AML [8]. The time dependence of contact degree F, effective temperature T eff of the primary (solid) and the secondary (dashed), together with the ratio of spin angular momentum to orbital angular momentum J rot /J orb , the luminosity transfer rate ∆L, the total mass, M tenv , contained in convective envelopes, and rate of AML [8].…”
Section: Structure and Evolution Of W Uma-type Systemsmentioning
confidence: 99%
“…This contact binary eventually coalesces into a single star (Webbink 1976;Eggleton 2000;Li et al 2005). If both components are on the main sequence, their remnant is also a main-sequence star and evolves similarly to a normal star with that mass.…”
Section: Coalescence Of Contact Binariesmentioning
confidence: 99%